Natural Syntax of Belfast English (I) Subject-Verb Agreement, (II) Imperative - Orešnik, Janez (Studia Anglica Posnaniensia, 2010)
The framework of this paper is Natural Syntax initiated by the author in the tradition of (morphological) naturalness as established by †Willi Mayerthaler and Wolfgang U. Dressler. Natural Syntax is a developing deductive theory. The naturalness judgements are couched in naturalness scales, which follow from the basic parameters (or “axioms”) listed at the beginningof the paper. The predictions of the theory are calculated in what are known as deductions, the chief components of each being a pair of naturalness scales and the rules governing the alignment of corresponding naturalness values. Parallel and chiastic alignment are distinguished and related to Henning Andersen’s early work on markedness. Natural Syntax is exemplified here with two syntactic phenomena found in Belfast English and partly deviating from Standard English: (I) subject-verb agreement, (II) the imperative. The language data are taken from Henry (1995), and close attention has been paid to the (TG)interpretations adduced in that monograph. Some recent work related to Natural Syntax: Orešnik (2007a-e, 2008a-c) and Orešnik and Cvetko-Orešnik (2009, only work written in English is mentioned).